Ovicidal activity of succinic acid isolated from sisal waste (Agave sisalana) against gastrointestinal nematodes of goats - Santos,Nathália Silva de Souza (2017)
ABSTRACT: This study was conducted to evaluate the in vitro anthelmintic activity of the succinic acid (SA) isolated from sisal waste against gastrointestinal nematodes of goats, using the egg hatching and larvae motility assays. In addition, potential cytotoxicity of SA on Vero cell cultures was investigated by means of MTT (3-4,5-dimethylthiazol-2-yl, 2,5diphenyltetrazolium bromide) test. The SA induced a significant inhibition of egg hatching (P<0.05) at all concentrations tested (60 to 250µg mL-1), and the concentrations to inhibit 50% (EC50) and 90% (EC90) values (mean ± standard deviation) were 90.3±2.8 and 130.6±3.5µg mL-1, respectively. The SA has not shown larvicidal activity. The SA was less toxic to the Vero cells, with the mean percentage of cell viability equal to 85±6.2% at the concentration of 130µg mL-1. The results suggested that SA has potential anthelmintic effect; although, more research is needed to confirm its activity in vivo.